Determinants of methicillin-resistant Staphylococcus aureus (MRSA) prevalence in the Asia-Pacific region: A systematic review and meta-analysis. (March 2019) - Lim, Wey Wen; Wu, Peng; Bond, Helen S.; Wong, Jessica Y.; Ni, Kaiwen; Seto, Wing Hong; Jit, Mark; Cowling, Benjamin J.
Highlights: Substantial disease burden is associated with MRSA resistance in Asia-Pacific. Study design explained variance in the reported MRSA resistance. No secular changes in MRSA resistance patterns in the Asia-Pacific region. Variation in MRSA resistance could not be explained by antimicrobial susceptibility testing methods. Abstract: Objectives: Published literature on methicillin-resistant Staphylococcus aureus (MRSA) in the Asia–Pacific region was reviewed to document the prevalence of MRSA in the region and to examine the impact of variability in study design on the reported MRSA prevalence data. Methods: This review included studies reporting MRSA prevalence between 2000 and 2016. Studies were excluded if they did not contain complete information on antimicrobial susceptibility testing (AST) methods. Primary outcomes were the proportion of MRSA among S. aureus isolates (resistance proportion) or among individual samples (prevalence). Results: A total of 229 studies in 19 countries/territories were included in the study. There was substantial heterogeneity in both outcomes (resistance proportion, I 2 = 99.59%; prevalence, I 2 = 99.83%), precluding pooled averages, and meta-regression analyses revealed that these variations were explained by country income status and participant characteristics but not by methodological differences in AST. Also, no significant secular changes in MRSA prevalence or resistance proportions in Asia-Pacific were found. Conclusion: The resistance proportions and prevalence of MRSA infections in Asia-Pacific are comparable with those reported in other regions with no significant secular changes in the past decade. Country income status and characteristics of the sample population explained more variation in the reported resistance proportions and prevalence of MRSA than methodological differences in AST across locations in the region.